Makna Ahli Kitab dalam Tafsir Al-Manar - Muslim Djuned; Nazla Mufidah (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2017)
Ahl al-Kitab is a term for those who believe and adhere to a religion that has a holy book that comes from Allah other than the Qur'an. In understanding the designation of the people of the book in the Qur'an, the scholars agree that they are Jews and Christians. However, they differ in terms of the scope of the meaning of the people of the book, some say that the people of the book are Jews and Christians of the descendants of the Children of Israel only, while others say that the people of the book are Jews and Christians whenever and wherever they are. This discussion will be examined using the maudhu'i method, in the form of library research, with descriptive data analysis. Based on the results of the study, the authors found the disclosure of the word expert in the book in the Qur'an as many as 11 forms, can be grouped as follows; first, the direct disclosure of the scribes; second, the same disclosure with the scribes; third, disclosure that is directed to the people of the book. Regarding the meaning of the people of the book, Rashid Rida agrees with the number of scholars, it's just that his opinion about the scope of the people of the book is wider than the previous scholars. In Tafsir al-Manar, the scope of the people of the book is not only limited to Judaism and Christianity but also includes other religions such as the Magi, Shabi'in, idol worshipers in India, China, and anyone who is similar to them. According to him, all these religions can be included in the scope of the people of the book because initially all religions adhered to monotheism. Ahli kitab adalah sebutan bagi yang mempercayai dan berpegang pada agama yang memiliki kitab suci yang berasal dari Allah selain al-Qur'an. Dalam memahami sebutan ahli kitab dalam al-Qur'an, para ulama sepakat bahwa mereka adalah Yahudi dan Nasrani. Namun mereka berbeda dalam hal cakupan makna ahli kitab, sebagian mengatakan ahli kitab adalah Yahudi dan Nasrani keturunan Bani Israil saja, sementara yang lain mengatakan bahwa ahli kitab adalah Yahudi dan Nasrani kapan pun dan di manapun mereka berada. Pembahasan ini akan diteliti menggunakan metode maudhu’i, berupa riset kepustakaan, dengan analisis data deskriptif. Berdasarkan hasil penelitian, penulis mendapatkan pengungkapan kata ahli kitab dalam al-Qur'an sebanyak 11 bentuk, dapat dikelompokkan sebagai berikut; pertama, pengungkapan ahli kitab secara langsung; kedua, pengungkapan yang sama dengan ahli kitab; ketiga, pengungkapan yang tertuju kepada ahli kitab. Mengenai makna ahli kitab, Rasyid Ridha sepakat dengan jumhur ulama, hanya saja pendapatnya tentang cakupan ahli kitab lebih luas dari ulama sebelumnya. Dalam Tafsir al-Manar, cakupan ahli kitab tidak hanya sebatas Yahudi dan Nasrani, tetapi juga mencakup agama-agama lain seperti Majusi, Shabi'in, penyembah berhala di India, Cina dan siapa saja yang serupa dengan mereka. Menurutnya, semua agama tersebut bisa dimasukkan dalam cakupan ahli kitab karena pada awalnya semua agama menganut tauhid.